Social capital in the Emirati family: A sociological study in the city of Kalba - Al-Droumki, Salma; Alhourani, Mohammed (Al-Adab Journal, 2025)
The research addressed the issue of social capital in the Emirati family in the city of Kalba. The research aims to identify the emotional support provided by the family, clarifying the nature of this material support provided by the family, identifying indicators of moral exchanges, and identifying the extent to which solidarity interactions take place within the family. And revealing the mechanisms of family communication and networking within the family, while identifying the relationship between the dimensions of the questionnaire and the strength of the social capital of the Emirati family in the city of Kalba.The research used a questionnaire prepared by the researchers, consisting of 32 indicators covering five dimensions. It achieved high standards of validity and reliability in the psychometric study conducted by the researchers. The research used the quantitative approach, as quantitative data was collected from a sample of 234 citizens of the city of Kalba in the Emirate of Sharjah. The results showed that the sample was distributed proportionately according to the demographic variables of the research, and their response showed a high overall rating of 5.16 on average for the dimensions of the questionnaire. On the items, the averages were between average and high. The results show high percentages of comfort, trust, and emotional support from the family to its members. On the other hand, the results showed evaluations Medium on the financial support dimension, where the average responses to the dimension items reached 4.66, and on the moral exchanges dimension, the average sample responses on the dimension reached 5.15, which is a high level. The general average reached 5.07 on the solidarity interactions dimension within the Emirati family, and the results showed a high average as well on the communication and networking dimension. The family score reached 5.15, which reflects a high level of communication and networking among family members in the city of Kalba. By studying the relationship between the dimensions of the questionnaire and the total score of the questionnaire, the results showed a strong correlation between all dimensions and the total score of the questionnaire, which highlights the great compatibility among Emirati family members in the city of Kalba. The research recommends with the contribution of social agencies to expand the concept of social capital, work to spread the culture of social capital, work to develop its components through various social means, and exploit all social and national upbringing institutions, in strengthening the components of the family’s social capital.